Learning Innovation Through the Development of CRT-Based E-LKPD to Train Elementary School Students' Understanding of Concepts and Creativity - Moh. Nur Faizi; Andika Adinanda Siswoyo (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research was motivated by the limited availability of teaching materials in schools and their insufficient alignment with students' learning needs, which has contributed to the low level of students' creative thinking skills. Therefore, this study aimed to develop a Culturally Responsive Teaching (CRT)-based E-LKPD for Indonesian language learning to enhance elementary school students' conceptual understanding and creative thinking skills. The developed product was evaluated in terms of its validity, effectiveness, and attractiveness. Product validity was determined through expert validation, while its effectiveness was assessed based on students' conceptual understanding and creative thinking test results. This study employed a research and development (R&D) approach using the 4D model, which consists of the define, design, develop, and disseminate stages. The results of the study show that the percentage of validity of E-LKPD based on learning design validation is 91.7%, teaching material validation is 93.3%, and material validation is 91.7%, all of which are included in the very valid category. The effectiveness is reviewed from the creativity of students classically reaching 100% of students in the minimum creative category, and the completeness of learning outcomes classically reaches 100% with complete criteria. The attractiveness was reviewed from the teacher's response obtained a percentage of 96.7%, while the student response reached 95%, both in the very interesting category. Based on these findings, it was concluded that E-LKPD teaching materials based on Culturally Responsive Teaching in Indonesian language learning to train the understanding of concepts and creative thinking skills of elementary school students were declared valid, effective, and interesting.